Next-generation sequencing and bioinformatic approaches to detect and analyze influenza virus in ferrets - Zhen Lin; Amber Farooqui; Guishuang Li; Gane KS Wong; Andrew L Mason; David Banner; Alyson A Kelvin; David J Kelvin; Alberto J Leon (Journal of Infection in Developing Countries)
Introduction: Conventional methods used to detect and characterize influenza viruses in biological samples face multiple challenges due to the diversity of subtypes and high dissimilarity of emerging strains. Next-generation sequencing (NGS) is a powerful technique that can facilitate the detection and characterization of influenza, however, the sequencing strategy and the procedures of data analysis possess different aspects that require careful consideration. Methodology: The RNA from the lungs of ferrets infected with influenza A/California/07/2009 was analyzed by next-generation sequencing (NGS) without using specific PCR amplification of the viral sequences. Several bioinformatic approaches were used to resolve the viral genes and detect viral quasispecies. Results: The genomic sequences of influenza virus were characterized to a high level of detail when analyzing the short-reads with either the fast aligner Bowtie2, the general purpose aligner BLASTn or de novo assembly with Abyss. Moreover, when using distant viral sequences as reference, these methods were still able to resolve the viral sequences of a biological sample. Finally, direct sequencing of RNA samples did not provide sufficient coverage of the viral genome to study viral quasispecies, and, therefore, prior amplification of the viral segments by PCR would be required to perform this type of analysis. Conclusions: the introduction of NGS for virus research allows routine full characterization of viral isolates; however, careful design of the sequencing strategy and the procedures for data analysis are still of critical importance.